Assédio sexual em uma instituição de ensino superior: a percepção das servidoras da Universidade Federal do Ceará (UFC) - Lima, Érica Cavalcante (2017)
Resumo Sexual harassment is framed as a disrespect to dignity sexual liberty quality of life at work and constitution of decent work Taking in count that is a crime that seems to choose it’s victims on purpose the women it’s valid highlight that it violates many rules that prohibit discrimination at work places Considering that women figure as an important amount of the quota of workers present in the most diverse spheres the study of this phenomenon it’s relevant to know what women have to say about it in order to call attention about it’s adverse effects in places where it occurs and the need of actions performed by the organizations to prevent this kind of problems in their spaces This paper aims to investigate the perspective of the public servers located at the Pró-Reitoria de Gestão de Pessoas – PROGEP of the Federal University of Ceará about the sexual harassment check which factors lead to the perception of the harassment seize the way the institution of work is perceived against this kind of practice and at last propose improvements in the work environment of the Organization emphasizing in the prevent of this crime To formulate this research of character qualitative it was applied a questionnaire to 58 public servers using in the analysis of the data the methodological procedures of the Speech of the Collective Subject We concluded this way that the workers evaluated show solid acknowledge about the concept of sexual harassment considering they know the characteristic elements that they understand the importance of a standing posture of the organizations in order to prevent these cases and that they realize their work environment the UFC as a place that doesn’t provide security to it’s workers in relation to sexual harassment We aspire that the results found may contribute to a better comprehension of what in fact is sexual harassment to help the Federal University of Ceará to proceed regarding this kind of work violence in order to prevent it and combat it as well as help future researches about the theme.